2020
DOI: 10.1080/23311975.2020.1806669
|View full text |Cite
|
Sign up to set email alerts
|

Family businesses restrict accrual and real earnings management: Case study in Saudi Arabia

Abstract: This paper investigates accrual earnings management (AEM) and real earnings management (REM) in family businesses (FB) in Saudi Arabia. Current literature indicates that minority rights are confiscated by the controlling shareholders in a business environment weak to protect investors. Based on this argument, considering the various implications of AEM and REM on family businesses, the results show evidence that family businesses in Saudi Arabia engaged in both types of earnings management during the period 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…Since it offers a transparent image of the sort of EM practices in GCC countries. Alhebri, and Al-Duais, (2020) examined the step-up earnings management (AEM) and real earnings management (REM) in family businesses (FB) in the Asian country. Current literature indicates that the dominant shareholders during business surroundings weak to shield investors confiscate minority rights.…”
Section: Critical Review Of the Literaturementioning
confidence: 99%
“…Since it offers a transparent image of the sort of EM practices in GCC countries. Alhebri, and Al-Duais, (2020) examined the step-up earnings management (AEM) and real earnings management (REM) in family businesses (FB) in the Asian country. Current literature indicates that the dominant shareholders during business surroundings weak to shield investors confiscate minority rights.…”
Section: Critical Review Of the Literaturementioning
confidence: 99%
“…On the other hand, concentrated ownership can bring the entrenchment effect and lead to a higher conflict of minority-majority shareholders. Some studies find the entrenchment effect in the family firms that lead to higher earnings management behavior (Alhebri and Al-Duais, 2020;Fatima et al, 2020;Martin et al, 2017;Di Meo et al, 2017;Yang, 2010). Other studies also show the insignificant role of the family to reduce minority-majority shareholders and fail to mitigate earnings management behavior, such as Vieira (2016), who does not find a significant effect of family firms on earnings management or Tai (2017), who find that family directors tend to engage more in accrual earnings management than REM one.…”
Section: Family Firmsmentioning
confidence: 99%
“…Furthermore, cross-listing is found to reduce the firms' control shareholders as a result of the widening of their investors base when listing overseas (Al-shamahi et al, 2017). The minority rights are found expropriated by the controlling ownership as they have a considerable ability to control other stakeholders (Alhebri & Al-Duais, 2020;Ghaleb et al, 2020). Studies have shown that firms originating from emerging markets characterized by weak governance suffer from ownership concentration (Moffett et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%